A brief introduction to genetics - Bellamy, Lawrence (Henry Stewart Talks, 2019)
The human genome, Genome editing, Why genetics is important today, Gregor Mendel’s pea experiments and his first law, Applications of Mendel’s first law in the context of dominant and recessive diseases in humans, Gregor Mendel’s dihybrid experiments and his second Law, DNA fingerprinting, Applications of Mendel’s second law